1973
DOI: 10.1159/000231056
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the Catecholamine Release in Anaphylactic, Anaphylatoxin, and Histamine Shock of Guinea Pigs

Abstract: (1) Antigen, in sensitized guinea pigs, produced a dose-dependent increase of the serum adrenaline concentrations, whereas the noradrenaline levels were not enhanced significantly. (2) The anaphylactic adrenaline release was diminished, but not prevented, by high doses of the antihistamine mepyramine. (3) Rat serum anaphylatoxin, in non-sensitized animals, provoked a significant increase in both the adrenaline and noradrenaline concentrations. Mepyramine abolished the adrenaline release, but not the noradrenal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1974
1974
1984
1984

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…Disodium cromoglycate (DSCG) increased the tissue cAMP only in sensitized but not in non-sensitized lungs.A similar inverse relationship existed in all our experimental condi tions between the tissue cAMP levels and the anaphylactic histamine re lease as was demonstrated by other authors in different test systems [Lichtenstein, 1971;Orange et al, 1971].The present study was done to learn whether catecholamine concen trations in the range of 10~9 to 1CL7 m, as found in the blood plasma of normal and anaphylactic guinea pigs [Piper et al, 1967;Bernauer et al, 1971 ;Bundschu et al, 1973], are sufficient to increase cAMP levels and to inhibit the anaphylactic histamine release in guinea pig lung tissue.We determined the activity of the adenylcyclase in chopped lung tissue from guinea pigs actively sensitized against ovalbumin, according to Krishna et al [1968]. The lung samples were preincubated for 2 h with 0.24 //Ci14C-adeninc and incubated for 15 min with isoprénaline, ad renaline, or noradrenaline.…”
supporting
confidence: 86%
“…Disodium cromoglycate (DSCG) increased the tissue cAMP only in sensitized but not in non-sensitized lungs.A similar inverse relationship existed in all our experimental condi tions between the tissue cAMP levels and the anaphylactic histamine re lease as was demonstrated by other authors in different test systems [Lichtenstein, 1971;Orange et al, 1971].The present study was done to learn whether catecholamine concen trations in the range of 10~9 to 1CL7 m, as found in the blood plasma of normal and anaphylactic guinea pigs [Piper et al, 1967;Bernauer et al, 1971 ;Bundschu et al, 1973], are sufficient to increase cAMP levels and to inhibit the anaphylactic histamine release in guinea pig lung tissue.We determined the activity of the adenylcyclase in chopped lung tissue from guinea pigs actively sensitized against ovalbumin, according to Krishna et al [1968]. The lung samples were preincubated for 2 h with 0.24 //Ci14C-adeninc and incubated for 15 min with isoprénaline, ad renaline, or noradrenaline.…”
supporting
confidence: 86%
“…Likewise, the H ereceptor mediated inhibitory effect of histamine in the rat uterus is due to local release of catecholamines from nerve endings [20,21]. Additional support for an H2-receptor dependent catecholamine release mechanism is found in the report of BUNDSCHU et al [22]. These investigators found that a significant portion of both anaphylactic and histamine-induced catecholamine release from guinea-pig adrenals is mepyramine resistant.…”
Section: Discussionmentioning
confidence: 96%